The The Effect of Store Image And Brand Awareness On Purchase Decisions With Purchase Intention As An Intervening Variable - Abdurrahman; Henny Welsa; Nonik Kusuma Ningrum (Journal of Economy, Accounting and Management Science (JEAMS), 2026)
The phenomenon at Kedai Kancakona Kopi shows that consumer purchasing decisions are influenced not only by the taste quality of coffee but also by store image, brand awareness, and positive experiences that shape purchase intention before making the final decision. This study aims to examine the effect of store image and brand awareness on purchase intention and its impact on purchasing decisions at Kedai Kancakona Kopi, Sumenep. A quantitative method was applied using purposive sampling with 111 respondents. Data were collected through an online questionnaire and analyzed using SPSS 24. The results indicate that store image and brand awareness significantly influence purchase intention both partially and simultaneously. Furthermore, purchase intention has a positive effect on purchasing decisions and also mediates the relationship between external factors and purchasing decisions. These findings emphasize that purchase intention is shaped not only by functional aspects but also by symbolic and emotional values of consumers. This study suggests that business practitioners should integrate the understanding of store image and brand awareness into marketing strategies to enhance consumer appeal and market competitiveness.